(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Saline soil remediation is a critical environmental challenge affecting agricultural productivity and ecosystem health. This research paper explores green and affordable solutions for saline soil remediation using phytoremediation. Phytoremediation leverages plants to absorb, accumulate, and stabilize salts from the soil, offering an environmentally sustainable and cost-effective method for soil recovery. This study evaluates various halophyte species, their mechanisms for salt tolerance, and their effectiveness in different soil conditions. Additionally, the paper discusses the integration of phytoremediation with other soil management practices to enhance overall soil health and productivity.